I Must Betray You - Sepetys, Ruta (New York : Philomel Books, 2022)
In a country governed by isolation, fear, and a tyrannical dictator, seventeen-year-old Cristian Florescu is blackmailed by the secret police to become an informer, but he decides to use his position to try to outwit his handler, undermine the regime, give voice to fellow Romanians, and expose to the world what is happening in his country. Includes author's note.
new ya book 2022 fall.
Includes bibliographical references.
Ages 12 and up.
Grades 7-9.
Keywords: Spies -- Fiction; Family life -- Romania -- Fiction; Dictatorship -- Fiction; Revolutions -- Fiction; Romania -- History -- Revolution, 1989 -- Fiction; Bucharest (Romania) -- History -- 20th century -- Fiction; Novels; Historical fiction